2018
DOI: 10.1111/asj.13114
|View full text |Cite
|
Sign up to set email alerts
|

Postruminal supply of amino acids enhances ghrelin secretion and lipid metabolism in feed‐deprived sheep

Abstract: Single amino acids (AA) feeding is gaining more attention for their functional roles beyond nutritional needs. This study aimed to describe the endocrine and metabolic responses to a single AA administration (at 10% of MP for maintenance) in 48 hr fasted sheep (n = 4) receiving, over continued 4 hr, a duodenal infusate of saline (control), glutamate (Glu), glutamine (Gln), lysine HCl (Lys), threonine (Thr), or valine (Val) in a 4 by 6 Youden square design with weekly intervals. Blood samples were collected at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Another possible reason for greater DMI for cows fed the RP-Glu is hormonal control. In a previous study, duodenal Glu infusion in 48-h fasted sheep increased plasma ghrelin concentration (Elsabagh et al, 2018). As ghrelin increases feed intake (Kojima et al, 1999), the greater DMI for the RP-Glu treatment might be mediated by ghrelin.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Another possible reason for greater DMI for cows fed the RP-Glu is hormonal control. In a previous study, duodenal Glu infusion in 48-h fasted sheep increased plasma ghrelin concentration (Elsabagh et al, 2018). As ghrelin increases feed intake (Kojima et al, 1999), the greater DMI for the RP-Glu treatment might be mediated by ghrelin.…”
Section: Discussionmentioning
confidence: 74%
“…Glutamate is considered as a NEAA, and NRC (2001) does not establish its dietary requirement for dairy cows. However, previous studies reported that postruminal Glu infusion increased plasma Glu concentration in 48-h fasted sheep (Elsabagh et al, 2018) and feed restricted mid-lactation cows (Ansia et al, 2017). Similarly, we observed that cows fed the RP-Glu diet had greater plasma Glu concentration only right after calving.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation